DRIS norms for ‘Keitt’ mango in the Brazilian semiarid region: diagnosis and validation - Tullio, Leonardo; Rozane, Danilo Eduardo [UNESP] (FapUNIFESP (SciELO), 2022)
Nutritional standards based on long-term data improve the nutritional diagnosis of the crop, as they make norms more precise and establish more refined criteria. This study aimed to evaluate the nutritional status of the mango crop using the DRIS methodology to identify nutritional limitations and validate norms. A da-tabase of 202 commercial plots was used, whose leaves were collected in the floral induction period between 2011 and 2018 in the Brazilian semiarid region. The productivity of 'Keitt' mango under the Brazilian semiarid conditions was not related to NBI-DRIS. Nutrient concentration presents positive and significant relationship with the respective DRIS indices, enabling the determination of the balance point, establishing a nutritional standard and enabling the use of foliar diagnosis for the variety. The order of nutrients with the highest frequency of limitations due to lack, in decreasing order, was: Zn > Al > Na > Cu > S > B > Mn > P = K > Fe > Ca > N > Mg, and limitation due to excess, in decreasing order was: Fe > Na > Mg > Al > Cu > B = N > S > Ca > P = K > Zn > Mn.
Normas DRIS para manga ‘Keitt’ no Semiárido brasileiro: Diagnose e validação
Keywords: Floral induction; Mangifera indica; Nutritional diagnosis